Aerogel-surfactant nanofluid system and preparation method and application thereof, and method for increasing formation gas storage capacity
By using the combination of hydrophobic silica aerogel nanoparticles and surfactant, an aerogel-surfactant nanofluid system is formed, which solves the problems of low solubility and strong fluidity of gas in the displacement liquid, and achieves the The efficient storage of gas in the formation is achieved.
Patent Information
- Application Number
- CN202411388188.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing carbon dioxide/hydrogen injection and formation storage technology faces problems such as low solubility, strong fluidity, gravity stratification and foam instability in the displacement liquid, resulting in low effective permeability and storage rate of gas in the formation. .
The combination of hydrophobic silica aerogel nanoparticles and surfactants is used to form an aerogel-surfactant nanofluid system. Through the synergistic effect of its porous structure and surfactant, the solubility and foam stability of the gas are improved. , reduce the gravity stratification effect.
The solubility and stability of gas in the formation are significantly improved, the fluidity and gravity layering effect of gas are reduced, thereby achieving efficient gas storage and improving storage efficiency by 75%.
Smart Images

Figure CN118879292B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of formation gas storage, and in particular to an aerogel-surfactant nanofluid system, a preparation method and application thereof, and a method for increasing the storage capacity of formation gas. Background Art
[0002] Mitigating greenhouse gas (such as carbon dioxide) emissions and developing clean energy (such as hydrogen energy) have become urgent tasks for addressing climate change and achieving sustainable development. Carbon dioxide capture, utilization and storage (CCUS) technology is considered one of the most promising solutions because it can store carbon dioxide on a large scale while obtaining economic benefits. Injecting carbon dioxide into depleted oil and gas reservoirs for enhanced steam / gas recovery (CO2-EOR / EGR) can not only achieve geological storage of carbon dioxide, but also significantly improve oil and gas recovery and energy efficiency.
[0003] On the other hand, hydrogen energy, as a clean, efficient and renewable secondary energy source, has attracted much attention in the process of achieving carbon neutral energy transformation. Since hydrogen is in gaseous form at room temperature and pressure and cannot be stored stably for a long time, it is necessary to develop safe and reliable underground storage methods to ensure the supply of hydrogen energy. Injecting hydrogen into underground spaces (such as depleted oil and gas reservoirs, salt caverns, etc.) for storage is expected to be an effective way.
[0004] However, existing carbon dioxide / hydrogen injection and formation storage technologies face many challenges. First, as a non-polar small molecule gas, carbon dioxide / hydrogen has low solubility in injection fluids (such as injected water) and crude oil gas, making it difficult to achieve efficient dissolution capture. Secondly, carbon dioxide / hydrogen has strong mobility in the formation, and suffers from severe adverse flow behaviors such as gravity stratification and fingering. Thirdly, conventional carbon dioxide / hydrogen foams are prone to instability and rupture under high temperature and high pressure conditions. All of the above problems restrict the effective storage and sealing rate of gas in the formation.
[0005] To solve these technical problems, traditional methods often use surfactants (such as SDS) to generate gas foam to increase viscosity, or add nanoparticles to enhance foam stability. However, these methods cannot fundamentally solve the solubility problem of gas in displacement fluids, and it is difficult to simultaneously deal with multiple challenges such as gravity stratification and foam instability. Therefore, they still cannot fully meet the requirements of efficient formation storage of carbon dioxide / hydrogen. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an aerogel-surfactant nanofluid system and its preparation method and application, as well as a method for increasing the amount of gas stored in the formation. The present invention utilizes a combination of hydrophobic silica aerogel nanoparticles and surfactants, which can not only greatly enhance the solubility of gases (such as carbon dioxide, hydrogen, etc.) in the injection fluid, but also form a gas foam system with excellent stability, and overcome the influence of gravity stratification on displacement efficiency, thereby achieving efficient storage and economical exploitation of gases in the formation. This technology can be widely used in many fields such as carbon dioxide capture and storage, underground storage of hydrogen energy, and oil and gas exploitation.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] An aerogel-surfactant nanofluid system comprises hydrophobic silica aerogel nanoparticles, a surfactant and water, wherein the concentration of the surfactant is 0.1-0.5wt%, the mass ratio of the hydrophobic silica aerogel nanoparticles to the surfactant is 1-3:1, and the surfactant is sodium dodecyl sulfate.
[0009] Preferably, the concentration of the surfactant is 0.5 wt %.
[0010] Preferably, the hydrophobic silica aerogel nanoparticles are porous materials, and the hydrophobic silica aerogel nanoparticles have an average particle size of 15-25 nm, a pore size of 40-60 nm, a porosity of 90-95%, and a specific surface area of 600-800 m 2 / g, density 0.25g / cm 3 .
[0011] Sodium dodecyl sulfate is abbreviated as SDS. The aerogel-surfactant nanofluid system is an aerogel-SDS nanofluid system.
[0012] Preferably, the aerogel-surfactant nanofluid system has the following properties: under the conditions of 323K and 30MPa, the dissolved fraction of carbon dioxide can reach 0.03407, which is 51.2% and 55.1% higher than that of the single SDS solution (0.02253) and the pure injection solution (0.02197), respectively.
[0013] Preferably, the method for preparing hydrophobic silica aerogel nanoparticles comprises the following steps:
[0014] (1) Prepare the reaction solution:
[0015] Tetraethyl orthosilicate (TEOS), anhydrous ethanol, deionized water and concentrated hydrochloric acid are mixed and stirred to form a homogeneous solution;
[0016] (2) Hydrolysis reaction:
[0017] The homogeneous solution is allowed to stand at room temperature for 8 to 24 hours to obtain a hydrolyzate, so that TEOS is completely hydrolyzed to generate silanol and ethanol byproducts;
[0018] (3) Acid-catalyzed gelation:
[0019] Adding ammonia water dropwise to the hydrolyzate to initiate a silanol polymerization reaction under acid catalysis to form a wet silica gel, wherein the molar ratio of TEOS to ammonia water is 1:(0.2-0.4);
[0020] (4) Aging:
[0021] The wet silica gel freshly obtained in step (3) is placed in an ethanol solution and aged at 50-70° C. for 3-5 days to obtain an aged silica gel to increase the porosity and specific surface area;
[0022] (5) Hydrophobic modification:
[0023] Adding a hydrophobic modifier, alkylchlorosilane, to the aged silica gel solution in step (4), and performing a hydrophobic modification reaction under reflux conditions to enrich the inner wall of the gel pores with hydrophobic groups, thereby obtaining a hydrophobically modified silica gel;
[0024] (6) Drying:
[0025] The hydrophobically modified silica gel is dried under supercritical conditions of 60°C and 9MPa to prepare a hydrophobic silica aerogel nanoparticle product.
[0026] Preferably, in step (1), the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water, and concentrated hydrochloric acid is 1:(3-5):(3-5):(0.005-0.02). Further preferably, 4 mol of anhydrous ethanol, 4 mol of deionized water, and 0.01 mol of concentrated hydrochloric acid are added per mol of TEOS.
[0027] Preferably, the acid-catalyzed catalyst in step (3) is hydrochloric acid, the reaction temperature is 20°C to 30°C, and the reaction time is 8 hours to 24 hours. Further preferably, 0.28 mol of aqueous ammonia is added dropwise per mol of TEOS.
[0028] Preferably, in step (5), the molar ratio of TEOS to the hydrophobic modifier is 1:(0.3-1.0).
[0029] More preferably, 0.5 mol of trimethylsilyl chloride is added per mol of TEOS.
[0030] In step (6), the hydrophobically modified silica gel is placed in a critical point drying device using critical point carbon dioxide or other appropriate drying medium.
[0031] The room temperature in the present invention generally refers to 20-30°C.
[0032] The present invention also provides a method for preparing aerogel-surfactant nanofluid, the steps of which are as follows:
[0033] The surfactant is dissolved in water, and then hydrophobic silica aerogel nanoparticles are added and dispersed by ultrasound or high shear to obtain an aerogel-surfactant nanofluid with a surfactant concentration of 0.1-0.5wt% and a mass ratio of hydrophobic silica aerogel nanoparticles to surfactant of 1-3:1.
[0034] The present invention also provides the use of the above-mentioned aerogel-surfactant nanofluid in increasing the storage capacity of formation gas. Preferably, the gas is hydrogen or carbon dioxide.
[0035] The present invention also provides a method for increasing the storage capacity of formation gas, wherein the prepared aerogel-surfactant nanofluid system is injected into the formation where the gas is to be stored through an injection device; while injecting the nanofluid system, the gas to be stored is injected into the underground formation, so that the gas is fully in contact with the nanofluid system to form a stable gas foam.
[0036] The nanofluid system significantly improves the solubility and stability of gas in underground formations by forming stable gas foam, reduces gas mobility and gravity stratification effects, and thus achieves efficient gas storage.
[0037] Preferably, the gas to be sealed includes carbon dioxide or hydrogen.
[0038] Beneficial effects of the present invention:
[0039] (1) The present invention provides a method for increasing the gas storage capacity of a formation by using a combination of hydrophobic silica aerogel nanoparticles and a surfactant. The porous structure of the hydrophobic silica aerogel nanoparticles and the synergistic effect with the surfactant are used to adsorb and dissolve a variety of gas molecules to form a highly stable gas foam displacement system, thereby achieving efficient storage of a variety of gases in the formation.
[0040] (2) The method of the present invention can improve the solubility of gases such as carbon dioxide and hydrogen in aquifers, promote gas foam stability and enhance oil / gas recovery efficiency.
[0041] (3) The nanofluid has the following properties: under the conditions of 323K and 30MPa, the dissolved fraction of carbon dioxide can reach 0.03407, which is more than 50% higher than that of single SDS solution and pure injection fluid; the carbon dioxide permeability continues to decrease during the injection process, and the final carbon dioxide residual saturation is as high as 93.3%, and the storage efficiency is increased by 75%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a TEM image of hydrophobic silica aerogel nanoparticles.
[0043] Figure 2 It is the particle size distribution histogram and cumulative curve of hydrophobic silica aerogel nanoparticles.
[0044] Figure 3 is the isothermal N2 adsorption-desorption curve of hydrophobic silica aerogel nanoparticles.
[0045] Figure 4 is the pore size distribution curve of hydrophobic silica aerogel nanoparticles.
[0046] Figure 5 is the foam half-life of SDS.
[0047] Figure 6 is the foam half-life of the aerogel-SDS nanofluid system. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further explained below in conjunction with the examples. Unless otherwise specified, the raw materials used in the specific implementation methods of the present invention are all common commercial products.
[0049] The hydrophobic silica aerogel nanoparticles are prepared according to the following method:
[0050] (1) Prepare the reaction solution:
[0051] Tetraethyl orthosilicate (TEOS), anhydrous ethanol, deionized water and concentrated hydrochloric acid are mixed at a material ratio of 4 mol ethanol, 4 mol water and 0.01 mol hydrochloric acid per mol TEOS, and stirred to form a homogeneous solution;
[0052] (2) Hydrolysis reaction:
[0053] The homogeneous solution was allowed to stand at room temperature for 12 hours to obtain a hydrolyzed solution, and TEOS was completely hydrolyzed to generate silanol and ethanol by-products.
[0054] (3) Acid-catalyzed gelation:
[0055] Ammonia water was added dropwise to the hydrolyzate (0.28 mol of ammonia water was added per mol of TEOS) to initiate silanol polymerization under acid catalysis (concentrated hydrochloric acid) to form wet silica gel. The silanol polymerization reaction temperature was 25°C and the reaction time was 1.5 hours.
[0056] (4) Aging:
[0057] The freshly prepared wet silica gel was placed in an ethanol solution and aged at 60° C. for 4 days to obtain an aged silica gel to increase the porosity and specific surface area.
[0058] (5) Hydrophobic modification:
[0059] Add trimethylchlorosilane, a hydrophobic modifier, to the aged silica gel solution, and perform a hydrophobic modification reaction under reflux conditions to enrich the hydrophobic groups on the inner wall of the gel pores. Add 0.5 moles of trimethylchlorosilane per mole of silanol to obtain a hydrophobically modified silica gel.
[0060] (6) Drying:
[0061] The hydrophobically modified silica gel is placed in a critical point drying device and dried using critical carbon dioxide or other appropriate drying media under supercritical conditions of 60°C and 9MPa to prepare a hydrophobic silica aerogel nanoparticle product.
[0062] Density test:
[0063] The density of hydrophobic silica aerogel nanoparticles was measured using a pycnometer. The weight of the pycnometer filled with water was M1 (g), the weight of the hydrophobic silica aerogel nanoparticles was M2 (g), and the weight of the solid added to the pycnometer filled with water was M3 (g). The material density ρ was calculated by formula (1):
[0064] (1)
[0065] Where: M 1——The weight of the pycnometer when it is filled with water, g;
[0066] ρ w ——Density of water, g·cm -3 ;
[0067] M 2——weight of hydrophobic silica aerogel nanoparticles, g;
[0068] M 3 – Total weight of the solid after adding it to the pycnometer filled with water, g.
[0069] Particle size test:
[0070] TEM images of hydrophobic silica aerogel nanoparticles Figure 1 As shown, the particle size distribution histogram and cumulative curve are as follows Figure 2 According to the image and particle size distribution histogram, the particle size of the material is mainly concentrated in the range of 15-25nm.
[0071] Pore diameter and specific surface area test:
[0072] The specific surface area and pore size distribution of the sample are tested by N2 adsorption desorption instrument. The clean and dried sample is placed in the adsorption tank, and nitrogen is passed through at a constant speed under variable pressure conditions. The volume of N2 adsorbed in the material is calculated according to the material balance law. The test results (such as Figure 3 , 4 The adsorption-desorption curves obtained by the method (shown in Figure 2) were imported into the mathematical model, and the pore size and specific surface area were calculated using the BJH formula and the BET method. According to the classification of nitrogen adsorption-desorption isotherms by the International Union of Pure and Applied Chemistry, the shape of this type of adsorption isotherm belongs to the IV type isotherm. At higher P·P0 -1 In the region, the adsorbate undergoes capillary condensation, the isotherm rises rapidly, and adsorption hysteresis occurs. The results show that the pore size distribution is in the range of 40-60nm, and the specific surface area is about 750m 2 ·g -1 . Porosity test:
[0073] Weigh a hydrophobic silica aerogel nanoparticle with a mass of m1 in the air, immerse it completely in kerosene for 1 hour, take it out, rinse the residual oil droplets on the surface with n-hexane solution, and dry it naturally. The mass at this time is weighed as m2. The hydrophobic silica aerogel nanoparticles that have completely absorbed kerosene are immersed again in a measuring cylinder filled with kerosene. The volume of kerosene overflowing from the measuring cylinder is V. The porosity of the hydrophobic silica aerogel nanoparticles is expressed as:
[0074] (2)
[0075] In the formula, 𝛷 ——Material porosity, %;
[0076] m 1——Mass of dry hydrophobic silica aerogel nanoparticles, g;
[0077] m 2——Mass of hydrophobic silica aerogel nanoparticles after saturation with kerosene, g;
[0078] ρ o ——Density of kerosene, g·cm -3 ;
[0079] V ——The volume of kerosene overflowing from the measuring cylinder, mL.
[0080] Based on the above test results, the average particle size of the hydrophobic silica aerogel nanoparticles obtained is 15-25nm, the pore size is 40-60nm, the porosity is 92.5%, and the specific surface area is 750m 2 / g, density 0.25g / cm 3 , which is hydrophobic.
[0081] Example 1
[0082] Preparation of aerogel-surfactant nanofluid with a mass ratio of hydrophobic silica aerogel nanoparticles to SDS of 3:1:
[0083] (1) Preparation of surfactant solution: Dissolve anionic surfactant sodium dodecyl sulfate (SDS) in water to obtain an SDS solution with a concentration of 0.5 wt%.
[0084] (2) Dispersing hydrophobic silica aerogel nanoparticles: adding the prepared hydrophobic silica aerogel nanoparticles to the SDS solution obtained in step (1) so that the mass ratio of the hydrophobic silica aerogel nanoparticles to the SDS is 3:1, and dispersing by ultrasound or high shear to form a stable aerogel-surfactant nanofluid.
[0085] Example 2
[0086] Preparation of aerogel-surfactant nanofluid with a mass ratio of hydrophobic silica aerogel nanoparticles to SDS of 1:1:
[0087] (1) Preparation of surfactant solution: Dissolve anionic surfactant sodium dodecyl sulfate (SDS) in water to obtain an SDS solution with a concentration of 0.5 wt%.
[0088] (2) Dispersing hydrophobic silica aerogel nanoparticles: adding the prepared hydrophobic silica aerogel nanoparticles to the SDS solution in step (1) so that the mass ratio of the hydrophobic silica aerogel nanoparticles to the SDS is 1:1, and dispersing by ultrasound or high shear to form a stable aerogel-surfactant nanofluid.
[0089] Example 3
[0090] Preparation of aerogel-surfactant nanofluid with a hydrophobic silica aerogel-SDS mass ratio of 1.5:1:
[0091] (1) Prepare surfactant solution: dissolve anionic surfactant sodium dodecyl sulfate (SDS) in water to obtain a 0.5 wt% SDS solution.
[0092] (2) Dispersing hydrophobic silica aerogel nanoparticles:
[0093] The prepared hydrophobic silica aerogel nanoparticles are added to the above SDS solution so that the mass ratio of the hydrophobic silica aerogel nanoparticles to SDS is 1.5:1, and dispersed by ultrasound or high shear to form a stable aerogel-surfactant nanofluid.
[0094] Example 4
[0095] Preparation of aerogel-surfactant nanofluid with a hydrophobic silica aerogel-SDS mass ratio of 2:1:
[0096] (1) Preparation of surfactant solution: Dissolve anionic surfactant sodium dodecyl sulfate (SDS) in water to obtain an SDS solution with a concentration of 0.5 wt%.
[0097] (2) Dispersing hydrophobic silica aerogel nanoparticles: adding the prepared hydrophobic silica aerogel nanoparticles to the above-mentioned SDS solution so that the mass ratio of hydrophobic silica aerogel nanoparticles to SDS is 2:1, and dispersing by ultrasound or high shear to form a stable aerogel-surfactant nanofluid.
[0098] Comparative Example 1
[0099] SDS solution fluid: Dissolve SDS powder in water to prepare an SDS solution with a concentration of 0.5wt%.
[0100] Fluid performance test:
[0101] 1. Stability of gas foam
[0102] Test method: The foaming ability and stability of SDS and aerogel-SDS nanofluid systems were evaluated at normal pressure using a Waring blender. Specifically, SDS solutions and aerogel-SDS nanofluid solutions with different ratios were prepared through experimental design. 100 mL of each solution was transferred to a stirring cup and preheated to the specified temperature for 1 hour. CO2 gas was then introduced at a flow rate of 100 mL / min for 5 minutes, followed by mixing at a high-speed shear condition of 8000 rpm for 3 minutes. The generated foam was quickly transferred to a measuring cylinder and placed in a constant temperature water bath. The stability of the foam was evaluated by measuring the foam stability index-drainage half-life, that is, the time required for 50 mL of water to drain. All experiments were repeated three times.
[0103] Depend on Figure 4 , Figure 5It can be seen that the half-life of a single SDS foam decreases sharply with increasing temperature, and is 62.4% shorter at 140°C than at 30°C. The aerogel-SDS foam system exhibits extremely high thermal stability. When the aerogel-SDS mass ratio is 1.5:1 (Example 3), the half-life only decreases by 6.36% in the range of 30-140°C. The foam can achieve the best performance. Excess SDS will shorten the foam half-life, while excess aerogel will reduce the foam viscosity, which is not conducive to displacement. In Examples 1, 2, and 4, when the aerogel-SDS mass ratio is 3:1, 1:1, and 2:1, respectively, the half-life decreases by 10.34%, 9.21%, and 8.82% in the range of 30-140°C, respectively.
[0104] The reason why aerogel-SDS is more stable is that aerogel nanoparticles form an insulating layer on the surface of the foam liquid film, effectively blocking the heat from penetrating into the internal foam. At the same time, the synergistic effect of aerogel and SDS optimizes the physical and chemical properties of the foam system, such as interfacial tension and viscoelasticity, to achieve excellent stability.
[0105] 2. To evaluate the gas storage performance of the foam system, a one-dimensional core flooding experiment was carried out.
[0106] Experimental steps: First, formation water was prepared and SDS solution (concentration of 0.5wt%) was prepared with this formation water. Then, silica aerogel nanoparticles degassed at 200°C were dispersed in the SDS solution to obtain aerogel-SDS nanofluid (the mass ratio of silica aerogel nanoparticles to SDS was 1.5:1). Next, sandstone samples were prepared using 80-120 mesh quartz sand, saturated with formation water after vacuum removal of air, and their porosity and permeability were evaluated. Finally, two different solutions (SDS solution only and aerogel-SDS nanofluid) were co-injected into sandstone samples with CO2 at flow rates of 0.2mL / min and 0.3mL / min, respectively, to conduct core displacement experiments. The amount of CO2 stored is equal to the amount of CO2 injected minus the amount of CO2 produced, and the storage efficiency is equal to the amount of CO2 stored divided by the amount of CO2 injected.
[0107] The results showed that when a single SDS solution was injected, the permeability reached a peak and then recovered rapidly, with the final residual carbon dioxide saturation being only 53.6%. When aerogel-SDS nanofluid was used, the permeability continued to decrease during the injection process, with the final residual carbon dioxide saturation reaching 93.3%, and the storage efficiency increased by 75%.
[0108] This improvement is due to two reasons: first, the porous structure of the aerogel itself can adsorb a large number of gas molecules; second, the aerogel-SDS foam system has excellent stability, which limits the flow of gas in the formation.
[0109] In addition to being applicable to carbon dioxide, this technology can also be extended to the underground storage of other gases such as hydrogen.
Claims
1. An aerogel-surfactant nanofluid system, characterized in that: The invention comprises hydrophobic silica aerogel nanoparticles, a surfactant and water, wherein the concentration of the surfactant is 0.1-0.5wt%, the mass ratio of the hydrophobic silica aerogel nanoparticles to the surfactant is 1-3:1, and the hydrophobic silica aerogel nanoparticles have an average particle size of 15-25nm, a pore size of 40-60nm, a porosity of 90-95%, and a specific surface area of 600-800m 2 / g, density 0.25g / cm 3 , the surfactant is sodium dodecyl sulfate.
2. The aerogel-surfactant nanofluid system according to claim 1, characterized in that: The concentration of the surfactant was 0.5 wt %.
3. The aerogel-surfactant nanofluid system according to claim 1, characterized in that: Hydrophobic silica aerogel nanoparticles were prepared by the following method: (1) Preparing a reaction solution: mix tetraethyl orthosilicate, anhydrous ethanol, deionized water and concentrated hydrochloric acid, and stir to form a homogeneous solution; (2) Hydrolysis reaction: The homogeneous solution is allowed to stand at room temperature for 8 to 24 hours to obtain a hydrolyzed solution, so that tetraethyl orthosilicate is completely hydrolyzed to generate silanol and ethanol by-products; (3) Acid-catalyzed gelation: Add ammonia water to the hydrolyzate to initiate silanol polymerization under acid-catalyzed conditions to form wet silica gel. The molar ratio of tetraethyl orthosilicate to ammonia water is 1:(0.2~0.4); (4) Aging: placing the wet silica gel obtained in step (3) in an ethanol solution and aging it at 50-70° C. for 3-5 days to obtain an aged silica gel; (5) Hydrophobic modification: adding a hydrophobic modifier, alkylchlorosilane, to the aged silica gel solution in step (4), and performing a hydrophobic modification reaction under reflux conditions to enrich the inner wall of the gel pores with hydrophobic groups, thereby obtaining a hydrophobically modified silica gel; (6) Drying: The hydrophobically modified silica gel is dried under supercritical conditions of 60°C and 9 MPa to prepare a hydrophobic silica aerogel nanoparticle product.
4. The aerogel-surfactant nanofluid system according to claim 3, characterized in that: In step (1), the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and concentrated hydrochloric acid is 1:(3-5):(3-5):(0.005-0.02).
5. The aerogel-surfactant nanofluid system according to claim 3, characterized in that: The acid-catalyzed catalyst in step (3) is hydrochloric acid, the reaction temperature is 20°C to 30°C, and the reaction time is 8 hours to 24 hours.
6. The aerogel-surfactant nanofluid system according to claim 3, characterized in that: In step (5), the molar ratio of tetraethyl orthosilicate to the hydrophobic modifier is 1:(0.3-1.0).
7. The method for preparing the aerogel-surfactant nanofluid system according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: dissolving a surfactant in water, then adding hydrophobic silica aerogel nanoparticles, and dispersing by ultrasonic or high shearing method to obtain an aerogel-surfactant nanofluid system with a surfactant concentration of 0.1-0.5wt% and a mass ratio of hydrophobic silica aerogel nanoparticles to surfactant of 1-3:
1.
8. Use of the aerogel-surfactant nanofluid system according to any one of claims 1 to 6 or the aerogel-surfactant nanofluid system prepared by the method according to claim 7 in increasing the storage capacity of formation gas.
9. A method for increasing the storage capacity of formation gas, characterized in that: The aerogel-surfactant nanofluid system described in any one of claims 1 to 6 or the aerogel-surfactant nanofluid system prepared by the method described in claim 7 is injected into the formation where the gas is to be sealed through an injection device. While injecting the nanofluid system, the gas to be sealed is injected into the underground formation so that the gas is fully in contact with the nanofluid system to form a stable gas foam.
Citation Information
Patent Citations
Application of phenyl glycidyl ether polymer serving as CO2 thickening agent
CN105331349A
Functional material production process and use method of material for process in oil and gas new energy
CN108485635A